Case series of accidental sanitizer consumption in children during COVID lockdown - Sankar, Reethika; Kadambi, Prahlad (International Journal of Contemporary Pediatrics, 2022)
Accidental consumption of unknown substances is common in pediatric age group due to the playful and curious nature of children. Children aged between 1-5 years are most vulnerable for such accidental consumption and thus parents are instructed to keep harmful substances out of reach of children, more so in this age group. With the advent of the COVID19 pandemic in 2020, sanitizers became a common name in most households, making children vulnerable for accidental consumption of them. This case series describes a series of Accidental Sanitizer Consumption in Children during the COVID Lockdown. 8 children presented with accidental consumption of sanitizer in June 2020. The mean age of the children who presented to the hospital was 3.37±1.06 years. Among the 8 children who presented to the hospital, 5 were female and 3 were male. The lethal dose of 1-Propanol and 2-propanol components are 2.8 g/kg and 2.1 g/kg respectively. None of the children had consumed the lethal dose. None of the children from our case series had complaints of confusion, drowsiness, shallow breathing, mucosal irritation, dizziness, headache and bradycardia as the quantity of handrub sanitizer below the toxic dose. Thus, we would like to reinforce responsibilities of parents towards preventing accidental consumption in children as it affects the community at large.